All Days 2013
DOI: 10.2118/165563-ms
|View full text |Cite
|
Sign up to set email alerts
|

Design and Field Evaluation of Tubing Deployed Passive Outflow Control Devices in SAGD Injection Wells

Abstract: The integration of horizontal wells and thermal oil recovery methods, such as Steam Assisted Gravity Drainage (SAGD), has enabled the economic exploitation of extra-heavy oil resources, mainly in Canada. The use of passive outflow control devices (OCDs) in SAGD wells adds steam injection points along the horizontal wellbore influencing steam placement and chamber growth; thus, potentially reducing the steam-to-oil ratio (SOR), productivity uncertainty and accelerating production.For designing OCD installations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The method consists of using temperature data obtained along the bore to extrapolate the steam pressure based on the known properties of saturated steam. This paper demonstrated that upper completions with FCDs can be successfully designed to inject steam more evenly along the lateral bore and also deliver more steam to the formation at a given injection pressure (Medina 2013).…”
Section: Completion Design/performancementioning
confidence: 99%
See 1 more Smart Citation
“…The method consists of using temperature data obtained along the bore to extrapolate the steam pressure based on the known properties of saturated steam. This paper demonstrated that upper completions with FCDs can be successfully designed to inject steam more evenly along the lateral bore and also deliver more steam to the formation at a given injection pressure (Medina 2013).…”
Section: Completion Design/performancementioning
confidence: 99%
“…The use of FCDs has been shown to help significantly improve the steam distribution along the lateral wellbore (Medina 2013). By using FCDs on the injection string, the steam chamber growth will be more balanced, and the risk of steam breakthrough can also be reduced.…”
Section: Introductionmentioning
confidence: 99%